2012
DOI: 10.1123/tsp.26.3.412
|View full text |Cite
|
Sign up to set email alerts
|

Group Dynamics in Sports: An Overview and Recommendations on Diagnostic and Intervention

Abstract: Working with teams and training groups is a common and major challenge for applied sport psychologists. This document is a position statement on the rationales, methods, and procedures of team-focused approaches in the practice of sport psychology. Furthermore, practice recommendations and research desiderata are discussed. To develop the paper, a consensus conference with nine experts from North America and Europe was held in Spring 2010. First, the paper presents the rationale for team-focused interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 71 publications
0
29
0
10
Order By: Relevance
“…There are a number of directions for future research. Kleinert et al [34] commented Running head: TEAM RESILIENCE REVIEW 10 that team-level topics are underrepresented in sport psychology and a need exists to address the lack of investigations focused on the everyday practices of teams. Team resilience provides researchers with many fruitful opportunities to tackle these gaps [4,35,36] Second, since team resilience is conceptualized as a dynamic process that evolves over time [7], research designs should reflect this conception.…”
Section: Future Researchmentioning
confidence: 99%
“…There are a number of directions for future research. Kleinert et al [34] commented Running head: TEAM RESILIENCE REVIEW 10 that team-level topics are underrepresented in sport psychology and a need exists to address the lack of investigations focused on the everyday practices of teams. Team resilience provides researchers with many fruitful opportunities to tackle these gaps [4,35,36] Second, since team resilience is conceptualized as a dynamic process that evolves over time [7], research designs should reflect this conception.…”
Section: Future Researchmentioning
confidence: 99%
“…The findings of this study revealed five main psychosocial processes, underpinning When developing excellence in teams, practitioners should consider utilizing the 25 framework proposed by Kleinert et al (2012). Specifically, they suggest that three situational 1 components determine the procedure, approach, and trust building when working with teams: 2 the sport psychologist himself or herself, the given tasks and demands, and the social and as a proactive approach to managing stressors and as part of a team's long-term development 10 rather than a short-term plan to address a crisis.…”
mentioning
confidence: 93%
“…In team sports, coaches are ultimately responsible for all aspects of the team as well as for the athletes' performance; therefore, their decisions and actions play a key role and influence both the individual level and the internal dynamics of their teams (Brandão & Carchan, 2010;Buceta, 2009;Kleinert et al, 2012). In this sense, a sports team is subject to various influences including individual differences among athletes (e.g., physical and mental skills, sports skills, psychological dispositions, etc.)…”
Section: Introductionmentioning
confidence: 99%